Implementasi Role Model Pada Praksis Pendidikan Pesantren di Pondok Pesantren Nurul Jadid dan Pondok Pesantren Nurul Qadim - Nur Aisyah; Nina Kholidah (Aafiyah: Jurnal Multidisiplin Ilmu, 2025)
The problems that occur in education will never end, especially in terms of character education. Because character becomes a measure of good and bad for someone in behavior. The application of the pesantren character education system is unique and different from each other. This then becomes quite an interesting thing to research. The purpose of this study is to analyze the process of internalizing role models in forming independent characters in Nurul Jadid Islamic Boarding School and Nurul Qadim Islamic Boarding School. This study used a phenomenological qualitative approach with a multi-site design, to answer the above questions. Research data is speech produced by researchers during the process of collecting data at the research location through observation, interviews, and documentation. The result of this study is that in forming an independent character in Nurul Jadid Islamic Boarding School and Nurul Qadim Islamic Boarding School through several processes such as being obliged to live in the pesantren, mingling the management with the students, making friends as models, limiting student meetings with family by the management at Nurul Jadid Islamic Boarding School and Nurul Qadim Islamic Boarding School. The difference between Nurul Jadid Islamic Boarding School and Nurul Qadim Islamic Boarding School lies in the management placement system and student attachment.